Hubungan antara Islam dan Kebudayaan Jawa - Saepudin, Ade (TSAQOFAH, 2024)
The discussion on the relationship between Islam and Javanese culture in Indonesia is intriguing. Culture is defined as a complex system that encompasses values, norms, beliefs, language, art, customs, institutions, technology, and creative products of humans. The focus od the research is on Javanese culture, which is prominent in Indonesia. The connection between Islam and Javanese culture is reflected in a long and diverse history, influenced by various ethnic groups, religions, and cultures united within one nation. This research adopts a literature review method, analyzing information from various literary sources such as books, research journals, and scholarly works. The conclusion indicates that the relationship between Islam and Javanese culture is inseparable, despite some contradictions. A thorough study of Islamic teachings is necessary to ensure proper integration of religious values and cultural traditions in the daily lives of the Javanese community.